Data compression in digital systems - Hoffman, Roy (Roy L.) (Digital multimedia standards series, 1997)
Beginning with early history and continuing to leading-edge applications and technology of data compression, this comprehensive account will enlighten a diverse audience. Information system managers, product and market analysis, and consultants who need to become acquainted with data compression technology and understand how it is changing the world of digital systems will gain valuable knowledge from the text. In addition, the book provides system designers, developers, engineers, programmers, and scientists with the knowledge needed to apply data compression in applications and products.